In Vivo Scintigraphic Imaging of Antitumor Effects by Combined Radioiodine Therapy and Human Sodium Iodide Symporter Gene Immunotherapy - Yun Choi; Yong Hyun Jeon; Jin Ho Paik; Jinkyung Ko; Dae Han Choi; June Key Chung; Chul Woo Kim (Molecular Imaging, 2010)
In a previous study, we demonstrated that pcDNA3.1/hNIS (human sodium iodide symporter) vaccination generated hNIS-associated CD8 + IFN-γ + (interferon-γ) T cells, which are known to be involved in antitumor immunity. However, the immune response induced was insufficient to control tumor growth in vivo, which required a novel approach to potentiate hNIS vaccination effects. In the present study, we administered 131 II radioiodine therapy prior to hNIS vaccination in CT26/hNIS tumor-bearing mice to facilitate the vaccine-induced immune response. We characterized hNIS-associated cytotoxic T-cell immune response and the antitumor effects induced by this 131 II + hNIS combination therapy. The survival rates of CT26/hNIS tumor cells were significantly reduced by 131 II treatment compared with the parental CT26 cells in vitro. 131 II + hNIS combination therapy stably suppressed tumor growth below or near the original tumor size level of initial treatment, achieving 100% survival rates. Specifically, 131 II + hNIS therapy enhanced IFN-γ production, hNIS-associated antitumor cytotoxic T-lymphocyte (CTL) response, and induced more dendritic cells but reduced T-regulatory cells in tumor masses. Collectively, these results suggest that combined therapy effectively enhances hNIS-associated antitumor immune response, leading to CT26/hNIS tumor growth inhibition and complete survival in Balb/C mice. These findings provide a novel and effective means of treating cancer.